RESEARCH ON VIRTUALIZATION TECHNOLOGIES - Muhamadov Odilbek Akmaljon o’g’li; Yaqubjonov Sardorbek (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Virtualization technologies have become an integral part of modern information technology, playing a key role in efficiently managing servers, networks, and data storage. These technologies enable optimization of infrastructure, cost reduction, and enhanced security. Moreover, virtualization facilitates disaster recovery, improves resource utilization, and supports seamless integration with cloud computing. It also empowers organizations to adopt innovative solutions like containerization and edge computing. This article analyzes the types of virtualization technologies, their benefits, challenges, and methods of practical application in diverse sectors, highlighting their role in shaping the future of IT infrastructure.